Інтродукційні популяції рідкісних видів рослин на ботаніко-географічних ділянках Національного ботанічного саду ім. М.М. Гришка НАН України - Melnik, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The problem of rare and endangered plant species protection ex situ are considered. The structure of introduced populations of some rare plant species in phytogeographical plots in M.M. Gryshko National Botanical Gardens is described.